The Impact of Traditional Peresean Sport on Physiological and Psychological Aspects and Its Role as Cultural Heritage: A Case Study of the Sasak Community in Lombok - Anam, khaerul; Andi Mulyan (UNIB Press, 2024)
Peresean is a traditional martial art deeply embedded in the culture of the Sasak people in Lombok. Beyond its role as public entertainment, Peresean plays a crucial part in preserving the cultural identity of the Sasak community and serves as a tool for resolving customary conflicts. However, over time, the understanding and practice of Peresean have diminished, particularly among younger generations, raising concerns about the potential loss of its valuable cultural and moral lessons. This research aims to emphasize the importance of preserving Peresean as cultural heritage and its potential as a solution to social issues like conflict and juvenile delinquency within the Sasak community. Using a qualitative case study approach in several Sasak communities, data were collected through field observations, in-depth interviews with local elders, and documentation of Peresean’s history and development. Findings indicate that Peresean, from a psychological perspective, is not only a form of entertainment but also an effective conflict resolution tool in Sasak society. It teaches values such as courage, sportsmanship, and social harmony. In conclusion, Peresean holds significant historical and social value, and its preservation is essential for maintaining Sasak cultural heritage. Cultural preservation efforts can help address social issues, ensuring community stability and cohesion in Lombok.